DAMPAK PERNIKAHAN DINI TERHADAP KESEHATAN ALAT REPRODUKSI WANITA - Yuspa Hanum; Tukiman Tukiman (Universitas Negeri Medan, 2015)
ABSTRACTOne of the important issues about reproduction healthy in internasional conference population and development (ICDP) di Kairo (1994), is sexuality and reproduction healthy . the purpose of marriage is obtaining descendants . Children obtained from the pregnancy is healthy reproductive at 20-30 years is a good age in reproduction cause the organs in body women had grown perfect. Early age marriage make more incidence, physical or psychological problem. Early age marriage make complicated in pregnancy and childbrith as pelvis narrow, hemorrhaging and death for both mother and child. And than early age marriage make stress to adolescent cause haven’t readiness in a mental. the purpose is know the description about impact early age marriage to the womens reproductive organs. Kata Kunci : Dampak pernikahan dini dan alat reproduksi wanita